2013
DOI: 10.1159/000342989
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Based Fine Needle Aspiration Biopsy of Papillary Thyroid Carcinoma: Logistic Regression Analysis with Conventional and New Cytomorphologic Features

Abstract: Objective: The morphological interpretation of liquid-based preparation (LBP) remains a diagnostic challenge due to altered cytomorphology with technical reason. Only a few published accounts of the cytopathological features needed for diagnosis of papillary thyroid carcinoma (PTC) on an LBP exist. We utilized the SurePath LBP system to evaluate conventional and newly recognized cytomorphologic features on histologically confirmed PTC to identify their potent diagnostic significance compared to benign follicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
23
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 30 publications
4
23
0
1
Order By: Relevance
“…[1][2][3] Although sample collection by FNAC is quite simple, interpretation of the collected cytologic material can be difficult. 4 It is obvious that these factors cause many cytomorphologic changes and consequently reduce diagnostic efficacy. Abundant vasculature of the thyroid organ itself and many of benign thyroid lesions causes a bloody or inflammatory background that may easily obscure follicular cells of diagnostic value.…”
mentioning
confidence: 99%
“…[1][2][3] Although sample collection by FNAC is quite simple, interpretation of the collected cytologic material can be difficult. 4 It is obvious that these factors cause many cytomorphologic changes and consequently reduce diagnostic efficacy. Abundant vasculature of the thyroid organ itself and many of benign thyroid lesions causes a bloody or inflammatory background that may easily obscure follicular cells of diagnostic value.…”
mentioning
confidence: 99%
“…Infolded "crenellated" nuclear membranes as described by Bellevicine et al 12 were, not surprisingly, more easily appreciated in the liquid-based preparation. Hobnail morphology can be identified in liquid-based preparations, 13,14 is a strong independent predictive factor for the diagnosis of PTC, 13 and is associated with tumor cell cytoplasmic vacuolation, cystic features, and presence of lymph node metastases. 14 Hobnail morphology may occur also in the context of oncocytic (oxyphilic) 2 and clear cell 15 change resulting from cytoplasmic accumulation of altered organelles (e.g., mitochondria) and/or stored substances such as lipids or glycogen.…”
mentioning
confidence: 99%
“…They concluded that LBC performed worse than CS for papillary thyroid carcinomas (PTC) but performed better for cases with a benign thyroid nodule [22]. These two methods have been compared in different studies, and the LBC methods have been shown to be quite effective in the evaluation of thyroid nodules [1,6,23,24,25,26,27]. …”
Section: Thyroidmentioning
confidence: 99%
“…The T1799A B-type RAF kinase (BRAF) mutation which leads to V600E amino acid substitution is the most common among more than 40 different BRAF mutations; it is almost exclusively detected in PTC (30-70% of cases) and in no other thyroid cancer types. BRAF mutation analysis of liquid-based thyroid FNAs improves the diagnostic specificity, particularly for the diagnosis of PTC [25,33,34,35,36,37]. A small percentage of PTC can behave more aggressively and lead to lymph node metastasis, extrathyroid invasion and even death.…”
Section: Thyroidmentioning
confidence: 99%
See 1 more Smart Citation